Rancang Bangun Aplikasi Manajemen Penjualan, Inventaris, dan Layanan Jasa Terintegrasi Menggunakan Metode Agile Scrum pada PT Mitra Maju Sejati - Rizqy Hisyam Mahendra; Rafly Rajwa Syahputra; Raga Fajar (CV. Shofanah Media Berkah, 2026)
Technological acceleration forces modern industries to swiftly shift toward digital systems to maintain business pace and customer satisfaction. This operational hurdle is precisely what PT Mitra Maju Sejati, an Air Conditioning (AC) service provider, struggles with, as its daily sales, inventory management, and technician scheduling remain fragmented. Consequently, stock discrepancies and field coordination bottlenecks between the administrative desk and on-site technicians frequently arise. To eliminate these manual inefficiencies, this study designs a web-based integrated management application using the Agile Scrum framework. Adopting a descriptive method alongside UML modeling tools (Use Case, Activity, Sequence, and Class Diagrams), the system was built progressively through dynamic sprint cycles. The outcome demonstrates that the platform successfully centralizes data streams in real-time, minimizes human logging errors, and simplifies field task tracking for the management. This implementation effectively transforms conventional, error-prone workflows into a highly agile and structured digital ecosystem.